2015
DOI: 10.4149/neo_2015_072
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum CA125 is an independent predictor for prognosis in operable patients with non-small cell lung cancer

Abstract: The role of serum CA125 and CEA in the prognosis of non-small cell lung cancer (NSCLC) remains controversial, especially in early stage patients, which need further clarification. Thus, in this study we carried out a large scale retrospective analysis of the prognostic value of CA125 and CEA in 645 patients with NSCLC, to explore their predictive value in the NSCLC. Patients who underwent curative surgical resection for NSCLC were from Zhejiang Cancer Hospital of China from 2006 to 2011. Microparticle enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A correlation between high baseline levels of CA 125 and worse survival in advanced stage (III–IV) NSCLC patients has been previously reported 18 . However, it was not conclusive in predicting relapse and failures 15, 17, 19 . Our study demonstrated that CA 125 is the only independent indicator for OS, PFS, LRFS, and DMFS, both in univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…A correlation between high baseline levels of CA 125 and worse survival in advanced stage (III–IV) NSCLC patients has been previously reported 18 . However, it was not conclusive in predicting relapse and failures 15, 17, 19 . Our study demonstrated that CA 125 is the only independent indicator for OS, PFS, LRFS, and DMFS, both in univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 45%
“…Compared with CEA and CYFRA 21‐1, there have been fewer studies on the relationship between CA 125 and survival. In operable NSCLC, serum CA 125 could be used as a tool to predict survival 15–17 . A correlation between high baseline levels of CA 125 and worse survival in advanced stage (III–IV) NSCLC patients has been previously reported 18 .…”
Section: Discussionmentioning
confidence: 95%
“…In China, the morbidity and mortality of lung cancer has been rising due to smoking and environmental deterioration in the past decades [36]. Despite the tremendous efforts and progress in lung cancer research, and the use of aggressive multimodal chemo- and radiotherapy, the overall treatment outcome for lung cancer patients remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, Ying et al 18 undertook FIGURE 1 Levels of epidermal growth factor (EGF) in bronchoalveolar lavage fluid. (A) Levels of EGF were significantly higher in patients with lung cancer than in patients with benign conditions (**p < 0.01 by t-test; the horizontal lines mark mean values).…”
Section: Discussionmentioning
confidence: 99%